CD4 T-Cell Dysregulation in Psoriatic Arthritis Reveals a Regulatory Role for IL-22 - Ezeonyeji, Amara; Baldwin, Helen; Vukmanovic-Stejic, Milica; Ehrenstein, Michael R. (Frontiers in Immunology, 2017)
Dysregulation of IL-22 has been associated with autoimmune diseases but divergent effects upon inflammation have hampered efforts to define its contribution to pathogenesis. Here we examined the role of IL-22 in patients with psoriatic arthritis (PsA). In the peripheral blood of PsA patients there was a decrease in IL-22+CD4+ T cells compared to healthy controls resulting in a heightened CD4+ IFNγ+/IL-22+ ratio accompanied by diminished CCR6 expression. IL-22 expressing cells were depleted primarily from the central memory CD4 T cell subset in PsA patients. Paradoxically IL-22 and particularly IFNγ production were elevated within a CD4+ T cell subset with phenotypic markers characteristic of naïve T cells (CD3+CD4+CD27+CD45RA+CCR7+CD95-IL-2Rβ-) from PsA patients with the highest IFNγ+/IL-22+ ratio of all the CD4 subsets. These unconventional “naïve” CD4+ T cells from PsA patients displayed some phenotypic and functional characteristics of memory cells including a marked proliferative response. Increased IFNγ production from these unconventional “naïve” T cells from PsA patients promoted greater expression of the chemo-attractant CXCL9 by HaCaT keratinocytes compared to their healthy counterparts. Treatment with anti-TNF therapy reversed these abnormalities in this T cell subset though did not affect the frequency of IL-22+ T cells overall. Furthermore, blockade of IL-22 enhanced the IFNγ mediated release of CXCL-9. These results reveal CD4+ T cell dysregulation in patients with PsA which can be reversed by anti-TNF and highlight the regulatory properties of IL-22 with important implications for therapeutic approaches that inhibit its production.